2018
DOI: 10.3390/polym10050489
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Delivery System for the Controlled Release~of Antimicrobial Peptides: Citropin 1.1 and Temporin A

Abstract: Antimicrobial peptides (AMPs) are prospective therapeutic options for treating multiple-strain infections. However, clinical and commercial development of AMPs has some limitations due to their limited stability, low bioavailability, and potential hemotoxicity. The purpose of this study was to develop new polymeric carriers as highly controlled release devices for amphibian peptides citropin 1.1 (CIT) and temporin A (TEMP). The release rate of the active pharmaceutical ingredients (APIs) was strongly dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Moreover, the qRT-PCR result explained that GERM CLEAN impaired virulence of S. mutans through downregulating expression of EPS-and acid-production related genes. e antibacterial activity of GERM CLEAN was preliminarily verified through the antibacterial ring test, but the diameter of inhibition zones formed by GERM CLEAN was not very stable, which varied from 8.4 mm to 12 mm according to our repeated tests, and we suspected that it might be related to the variety of the peptide stability [64][65][66][67][68][69], and this hypothesis needs further confirmation.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the qRT-PCR result explained that GERM CLEAN impaired virulence of S. mutans through downregulating expression of EPS-and acid-production related genes. e antibacterial activity of GERM CLEAN was preliminarily verified through the antibacterial ring test, but the diameter of inhibition zones formed by GERM CLEAN was not very stable, which varied from 8.4 mm to 12 mm according to our repeated tests, and we suspected that it might be related to the variety of the peptide stability [64][65][66][67][68][69], and this hypothesis needs further confirmation.…”
Section: Discussionmentioning
confidence: 97%
“…To improve AMPs administration, new polymeric carriers can be used as highly controlled release devices. Piotrowska et al [81] chose the peptides citropin 1.1 (CIT) and TA for their experiments. They found that the release rate of the active pharmaceutic ingredients (APIs) was strongly dependent on the API characteristics and the matrix microstructure.…”
Section: Temporin Amentioning
confidence: 99%
“…PCL-1 with X c of 50.5% that have a high content of non-charged macrocycles in their structures (ca. 35% [ 9 ]), thus the EE in this case was lower. In contrast, we noted higher EE values for MP-PCL-2 ( X c = 56.3%) with a lower content of macrocyclic chains (19% [ 9 ]).…”
Section: Resultsmentioning
confidence: 95%
“…This study is a continuation of our previous research [ 9 ] on the synthesis and investigation of the structural, physicochemical and biological properties of the PCLs matrices for prolonged peptide release. In this paper, medium-term delivery systems of citropin 1.1 (CIT, amino acids sequence: GLFDVIKKVASVIGGL) were prepared from poly(ε-caprolactone) (PCL) matrices using the solvent evaporation method.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation